Psychological stress levels and their relationship to emotional intelligence among nurses at the Oncology Center at Lattakia University Hospital" A field study" (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This field study aimed to examine the level of psychological stress and its relationship with emotional intelligence among nurses working at the Oncology Center in Al-Latakia University Hospital. It also investigated differences in stress and emotional intelligence based on marital status and age. The study adopted a descriptive method and included all 107 nurses in the center. Data were collected from a sample of 71 nurses.Results showed that the most significant stressor was the impact on social relationships, followed equally by work-related stress and stress from dealing with patients. In terms of emotional intelligence, the highest-rated dimension was self-esteem and personal value, followed by emotional regulation and flexibility, and finally, interpreting stress and difficult events.A statistically significant positive correlation was found between psychological stress levels and emotional intelligence dimensions. However, no significant differences were observed in stress or emotional intelligence based on marital status or age. The study highlights the importance of developing emotional intelligence skills to help nurses manage stress more effectively and enhance their professional performance.
Keywords: stress level, emotional intelligence.